Asymmetric imidazole/pyrene/pyrazine based D-π-A compounds showing visualized acidichromism and near-infrared electrochromism. Issue 49 (9th December 2015) - Ma, Bin-Bin; Feng, Gen-Feng; Zhao, Pei-Chen; Chang, Fei-Fan; Huang, Wei
Graphical abstract: Two asymmetric pyrene based D- π -A compounds (named asPyMB -1 andPyMB -2 ) have been synthesized and characterized, and they are found to show reversible protonation-triggered visualized acidichromism and near-infrared electrochromism. Highlights: Two asymmetric D- π -A compounds (PyMB -1 andPyMB -2 ) are described. They have the common imidazole/pyrene/pyrazine core. PyMB-1 andPyMB -2 display reversible acidichromism. The thin film ofPyMB -2 shows reversible NIR electrochromic behavior. Abstract: Two asymmetric imidazole/pyrene/pyrazine centered D- π -A compounds (PyMB -1 andPyMB -2 ), bearing 4-[ N, N -bis(4-methoxyphenyl)amino]phenyl/4-[ N, N -bis[4-(di-4-anisylamino)phenyl]amino]phenyl and didodecyloxybenzene terminals, have been synthesized and characterized in this work. It is found that the color of two compounds could change from light yellow to brown after the treatment with trifluoroacetic acid (TFA) in their CH2 Cl2 solutions, which could be detected by direct visual observation. In addition, the thin film of 4-[ N, N -bis[4-(di-4-anisylamino)phenyl]amino]phenyl terminated compound shows reversible electrochromic behavior accompanied by a color alteration from yellow to green under different bias voltages, which could be monitored by in situ UV–vis and near-infrared (NIR) spectroscopy.